The Effectiveness of Teaching Integrated Science Meterics on High Level Thinking for Junior High School Students Banda Aceh - Azwir; Muhammad Ridhwan; Nurul Akmal; Rubiah; Muliana; Ibrahim (Postgraduate, University of Mataram, 2024)
The aim of this research is to test the effectiveness of integrated science teaching materials for junior high schools, especially the theme of household health and environmental sanitation. The research design uses a quasi-experiment with Pretest-Posttest Control Group Design. The research was carried out at SMPN 6 Banda Aceh class VII. The sample was determined by purposive sampling. The treatment in the experimental group was learning that used integrated science teaching materials, while the control group used electronic school books. The instruments used are test items, learning observation sheets, and learning tools. Data analysis was carried out using Anava to test mean differences and Scheffe test to test the effectiveness of integrated science teaching materials. The results of the research show that there are differences in high-level thinking abilities between junior high school students who use integrated science teaching materials and students who use separate/individual science teaching models in the field of biological studies. Students can remember 13%, understand 15%, application 18%, analysis 30% and evaluation 25% for thinking achievement. Teaching using integrated science teaching materials is very effective in improving the high-level thinking abilities of students at SMP Negeri 6 Banda Aceh.